A Value Chain Framework for Assessment of Sustainable Practices in Manufacturing Firms - Pande, Bhavya; Kumar Adil, Gajendra (European Journal of Sustainable Development, 2019)
Manufacturers face the challenge of implementing and assessing sustainable practices in their organizations due to several factors including lack of availability of clear guidelines and tools. Porter and Kramer (2006) suggest a framework on how to capture the negative effects of an organization’s primary and support value chain activities on the environment and society. In this paper, the framework suggested by them has been suitably modified to capture and organize sustainable practices relevant to manufacturing firms. Accordingly, a number of sustainable practices are identified through a detailed analysis of literature and incorporated in the developed framework. Further, in order to validate the potential of the proposed framework to be used as an assessment tool, feedback was sought from a senior level professional from an internationally acclaimed research center with experience and proficiency in conducting sustainability audits in textiles and leather industry. Going forward, the validated framework will be administered to assess sustainable practices in select manufacturing organizations. This study is a part of an ongoing research on assessment of sustainability in manufacturing organizations. Keywords: Assessment of Sustainable Practices; Sustainable Value Chain Practices; Triple Bottom Line; Total Life Cycle Approach; Sustainable Manufacturing